PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN AUDIO LISTENING WORKSHEETS TERHADAP KETERAMPILAN MENYIMAK CERITA PENDEK SMA MUHAMMADIYAH 1 UNISMUH MAKASSAR - Dila, Dila Adelia Putri; A Rahman Rahim; Rahmatiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to demonstrate the effectiveness of using audio listening worksheets in improving short story listening skills of tenth-grade students at SMA Muhammadiyah 1 Unismuh Makassar. This study employed a quantitative experimental method using a pretest-posttest control group design. The study population was all tenth-grade students, with a sample size of 44 divided into an experimental and a control class. The research instruments consisted of a multiple-choice test (10 items) and an essay test (1 item), along with documentation. Data analysis used descriptive and inferential statistics, including tests for normality, homogeneity, and hypothesis testing. The results showed that the average pretest score in the control class decreased from 71.36 to 70.90 in the posttest. Conversely, the average pretest score in the experimental class increased from 70.90 to 82.27 in the posttest. This was accompanied by a decrease in the standard deviation, indicating consistent student learning outcomes. These findings demonstrate that the use of Audio Listening Worksheets has a positive and effective effect on improving students' short story listening skills)